2009
DOI: 10.1182/blood-2009-02-206557
|View full text |Cite
|
Sign up to set email alerts
|

Antigen sensitivity is a major determinant of CD8+ T-cell polyfunctionality and HIV-suppressive activity

Abstract: CD8 ؉ T cells are major players in the immune response against HIV. However, recent failures in the development of T cell-based vaccines against HIV-1 have emphasized the need to reassess our basic knowledge of T cell-mediated efficacy. CD8 ؉ T cells from HIV-1-infected patients with slow disease progression exhibit potent polyfunctionality and HIVsuppressive activity, yet the factors that unify these properties are incompletely understood. We performed a detailed study of the interplay between T-cell function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
233
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(262 citation statements)
references
References 58 publications
24
233
5
Order By: Relevance
“…In the case of viral infections, the increased efficacy of high avidity CTL results, at least in part, from their ability to recognize virus-infected cells very early after infection (22). The crucial involvement of high avidity CTL in the clearance of viruses and tumors has been confirmed in a number of studies (5,6,28,34,43,55,61,63). That said, there may be circumstances wherein lower avidity cells play a critical role.…”
mentioning
confidence: 96%
“…In the case of viral infections, the increased efficacy of high avidity CTL results, at least in part, from their ability to recognize virus-infected cells very early after infection (22). The crucial involvement of high avidity CTL in the clearance of viruses and tumors has been confirmed in a number of studies (5,6,28,34,43,55,61,63). That said, there may be circumstances wherein lower avidity cells play a critical role.…”
mentioning
confidence: 96%
“…Selection of high-avidity CD8 T cells correlates with control of viral infections and polyfunctional profiles as well as potent virussuppressive activity including HCV (16,17). Notwithstanding the intrinsic superior antiviral activity of higher avidity TCR CD8 T cells, low-avidity TCR polyfunctional CD8 T cells have been suggested to be more fit in providing disease control during chronic virus infection (18) and have been reported to reject tumors and can have less problems regarding immune pathology (19).…”
mentioning
confidence: 99%
“…As with chronic infections, such as HIV and HCV, as well as in cancer, the host may lose (by clonal exhaustion or other apoptotic mechanisms) the effector cells that are most critical for viral or tumor clearance (18). In the case of HCV, the high-avidity T cells have been suggested to control HCV infection (16,17); however, what remains unclear is whether low avidity T cells may contribute to antiviral mechanisms against the HCV-infected cells.…”
mentioning
confidence: 99%
“…It was proposed that a correlate of protection in HIV infection is the presence of T cells of high functional avidity and, further, that these high-avidity T cells also were of increased polyfunctionality (7,8). Interestingly, although we found that low vaccine Ag doses induced CD4 T cells of higher functional avidity and greater polyfunctionality (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Increasing the functional avidity of T cells in vivo through immunization is a promising strategy to increase vaccine efficacy against infectious diseases and tumors (3)(4)(5)(6)(7)(8)(9).…”
Section: N Ovel Vaccine Candidates Have Traditionally Been Evaluatedmentioning
confidence: 99%